The influence of member orientation on hollow section joint strength - Kelly, Robert (1998)
The influence of the member orientation on the strength of joints formed with square hollow sections is examined. The bird beak joint system is a relatively new truss arrangement for square hollow sections, where the chord and the brace have each been rotated by 45° about their own centreline axes. Based on previous experimental testing it has been suggested that this joint system leads to a stronger joint arrangement.